THE LONG RUN EFFECTS OF RENEWABLE AND PRIMARY ENERGY DEMAND ON GROWTH IN TURKEY (Third Sector Social Economic Review, 2019)
As the main objective, economic growth and development efforts increase the energy demand of all countries worldwide. Although an important part of the increasing demand is met by primary energy sources, the production and the consumption of renewable energy sources have risen in recent years. The aim of this study is to empirically analyze the effects of renewable and primary energy demand on economic growth and to determine causality relationships among related variables. In the analysis conducted using Turkey's 1965-2017 period data, Johansen co-integration and Dolado-Lütkepohl causality test with structural vector error correction model were used. According to the results, there is both co-integration relation on variables and unidirectional causality from energy demand to economic growth. In other words, a result that supports the growth hypothesis has found. Furthermore, according to the structural model results, renewable and primary energy consumption has positive effects on economic growth in the long run.
Keywords: Renewable energy; Primary energy; Growth; Causality; Cointegration; SVEC Model